Pengaruh Penerapan Penilaian Berbasis Kelas Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Akidah Akhlak - Sri Nurhamidah; Gilang Maulana Jamaludin (Al-Mau'izhoh : Jurnal Pendidikan Agama Islam, 2022)
This research is motivated by the teacher's assessment of student learning this is caused by the number of teachers assessing student learning outcomes using creative assessment, meaning that the success of religious education is solely based on a compassionate assessment, who has attended the lesson is considered to understand it. This study aims to apply classroom-based assessment to student learning outcomes. The method used in this research is descriptive method, technical analysis used in this research is validity test, reliability test and hypothesis testing. The population in this study were all students of MA Al Fajar Kalapadua while the research sample was taken from class X students of MA Al Fajar Kalapadua as many as 39 students. From the test results obtained ro (calculated) of 0.94 and the price of rt (table) by taking a significance level of 5% of 0.346. Because the value of ro (count) rt (table), then Ha is accepted and Ho is rejected. So it can be concluded that there is a significant correlation between the application of class-based assessment to student learning outcomes in learning aqidah morality.